2012
DOI: 10.15835/nbha4028055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cellulase and Pectinase Enzyme Treatments on Protoplast Isolation and Viability in Lilium ledebeourii Bioss.

Abstract: For overcoming interspecific incompatibility, protoplast combination method is a proper procedure for making a new plant with desired traits. For this purpose, protoplast preparation is a first and important step. Hence, experiments were conducted to evaluate various combinations of cellulose, pectinase and their treatment times on protoplast production and protoplast viability in Lilium ledebeourii Bioss. The results of experiment revealed that the protoplast yield was significantly affected by different trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…It is possible that the higher cellulase concentration used as over-digestion of explants resulted in the decreasing of protoplast yield (Zhu et al, 2005). Moreover, higher concentrations of enzymes might negatively influence the viable protoplasts (Chamani et al, 2012). Similar observations were obtained by Yao et al (2016) who reported that 1.0% cellulase R-10, 0.5% pectolyase Y-23 and 0.6 M mannitol (pH 5.8) was the optimum concentration used to obtain high yield of protoplast for sweet cherry (Prunus avium L.), 4.3x10 6 protoplasts/g FW of explants and 0.5% celluase onozuka RS10 and 0.5% macerozyme R-10 in combination was the suitable enzyme concentration for obtaining high protoplast yields of Citrus reticulata L. (Wulandari et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that the higher cellulase concentration used as over-digestion of explants resulted in the decreasing of protoplast yield (Zhu et al, 2005). Moreover, higher concentrations of enzymes might negatively influence the viable protoplasts (Chamani et al, 2012). Similar observations were obtained by Yao et al (2016) who reported that 1.0% cellulase R-10, 0.5% pectolyase Y-23 and 0.6 M mannitol (pH 5.8) was the optimum concentration used to obtain high yield of protoplast for sweet cherry (Prunus avium L.), 4.3x10 6 protoplasts/g FW of explants and 0.5% celluase onozuka RS10 and 0.5% macerozyme R-10 in combination was the suitable enzyme concentration for obtaining high protoplast yields of Citrus reticulata L. (Wulandari et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They found that 0.5% macerase and 1% cellulysin with 24 h of incubation time was the suitable condition. Chamani et al (2012) reported that a digestion period of 24 h resulted in the highest yield of protoplasts (6.65x10 5 protoplasts/g FW) from Lilium ledebeourii. In addition, incubation time of 24 h was the appropriate for isolation of protoplast from pine (Pinus Iambertiana) when treated with the combination of 0.15% onozuka, 0.05% rhozyme and 0.08% pectinase (David and David, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic preparations of pectin are also implemented in various pharma-based industries for the development of low-methoxy pectin that is beneficial for diabetic patients ( 14 , 16 ). Purified forms of pectinase, which are commercially isolated from different fungal species, have a great role in plant protoplast culture studies as they help to generate good yields of viable protoplast when treated with cellulose ( 17 ). However, like other enzymes, this one is also more activated during its commercial production at 30 to 50°C and a pH of 4.5 to 8.5, but the effectiveness is more specific to the source of particular microorganisms and other environmental factors ( 10 ).…”
Section: Introductionmentioning
confidence: 99%